(untitled) (Research, Society and Development, 2022)
The objective of this study was to identify the factors associated with negative self-perception of health in market workers in the city of Guanambi, BA, Brazil. It was a census and cross-sectional study, with data from the baseline research entitled "Accidents at work in market vendors and labor and health conditions: a prospective study", containing sociodemographic, labor, lifestyle profile, and data concerning the self-perception of health of 426 market vendors from the Municipal Market of the city of Guanambi, Bahia. Self-perception of health was investigated by the question: "how do you rate your current health status?". Sociodemographic and work characteristics, life habits, and health conditions were analyzed. The prevalence of negative self-perception of health was 54% among market workers, with a predominance among women (n=153, 58%), among those who had completed elementary school (n=166, 59.1%), with a not good work capacity (n=44, 81.5%), with symptoms of musculoskeletal problems (n=48, 70.6%) and who sought health services in the last 2 weeks (n=47, 81%). It was found that the negative self-perception of health among informal trade workers has a high prevalence compared to studies that address such perception in formal and informal workers, pointing to the need for health strategies for this vulnerable public.